On the road to wonderful? Bank restructuring after EMU - Christopher Hurst; Eric Perée; Mireille Fischbach (EIB Papers, 1999)
Throughout the industrialised world the banking sector has embarked on a programme of restructuring and consolidation. In Japan the severity of the banking crisis has recently forced both the banking sector and the authorities to recognise deep-rooted problems and to take decisive action. In North America, the banking landscape is also undergoing major changes. Segmentation of activities enshrined in the Glass-Steagall act is being reduced and most restrictions to interstate banking consolidation have been abolished. Similar developments also characterise the European banking scene. However, as long as European countries maintained their monetary sovereignty, the scope for cross-border banking consolidation was limited. The introduction of the euro may, therefore, usher a period of restructuring and consolidation in Europe. This paper discusses the restructuring of the banking sector in Europe and how it is affected by EMU. In order to identify the fundamental forces shaping the restructuring process, the next section looks back at the evolution of the banking industry over the last twenty years and how EMU interacts with these forces. Section 3 then focuses on the role of banks, their interaction with the capital markets and some idiosyncrasies of the European banking sector. Section 4 reviews the overall financial performance of banks to diagnose the potential strengths and weaknesses of European banks. Section 5 then turns to the discussion of the recent experience of consolidation and restructuring of the banking system on both sides of the Atlantic Ocean, while Section 6 attempts to map out the likely restructuring of the European banking industry in the coming years.
Keywords: 330; Europäische Wirtschafts- und Währungsunion; Bank; Wettbewerb; Reorganisation; Wirtschaftliche Anpassung; EU-Staaten